(untitled) (Bangladesh Journal of Botany, 2008)
Meiotic abnormalities and pollen sterility due to virus infection in Capsicum annuum L., Carica papaya L., Lablab purpureus L., Lycopersicon esculentum L., and Solanum melongena L. were studied. Comparison in with unaffected plants showed that virus infected plants, asynapsis, multivalents and lower chiasma frequencies were present. Frequencies of chromosomal irregularities and pollen sterility were high in virus infected plants. Â Key words: Virus infection, Cytological effect, Plant species doi:10.3329/bjb.v37i2.1734 Bangladesh J. Bot. 37(2): 207-209, 2008 (December)